2019
DOI: 10.7150/thno.33143
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Finely Tuned Albumin Nanoplatform based on Click Chemistry

Abstract: Albumin is one of the most attractive nanoplatforms for targeted imaging and drug delivery due to its biocompatibility and long circulation half-life. However, previously reported albumin-based nanoplatforms have shown inconsistent blood circulation half-life according to the modified methods, and the affecting factors were not well evaluated, which could hamper the clinical translation of albumin-based nanoplatforms. Herein, we developed a finely tuned click-chemistry based albumin nanoplatform (CAN) with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Studies on healthy rats have shown that [ 68 Ga]ABY-028, an albumin-binding domain protein-based imaging tracer for positron emission tomography, binds in vivo to albumin, acquires albumin circulatory behavior, and accumulates in liver, spleen, and in muscle tissues [ 75 ]. Similar data were published by Park and collaborators [ 76 ] who noticed effective accumulation of 64 [Cu]-labeled-click chemistry-based albumin nanoplatform conjugates in normal lung, liver, kidney, intestine, and heart with an over four-fold higher uptake than the tumor at 1 h post-injection. Zhong and collaborators [ 77 ] showed effective accumulation of anlotinib (an oral RTKI targeting VEGFR, PDGFR, FGFR, and c-Kit; Table 1 ) in female tumor-bearing mice.…”
Section: Diffusion and Abp-mediated Mechanisms Could Underlie The Accumulation Of Rtkis Bound To Albumin In Healthy Organs And Tissuessupporting
confidence: 87%
“…Studies on healthy rats have shown that [ 68 Ga]ABY-028, an albumin-binding domain protein-based imaging tracer for positron emission tomography, binds in vivo to albumin, acquires albumin circulatory behavior, and accumulates in liver, spleen, and in muscle tissues [ 75 ]. Similar data were published by Park and collaborators [ 76 ] who noticed effective accumulation of 64 [Cu]-labeled-click chemistry-based albumin nanoplatform conjugates in normal lung, liver, kidney, intestine, and heart with an over four-fold higher uptake than the tumor at 1 h post-injection. Zhong and collaborators [ 77 ] showed effective accumulation of anlotinib (an oral RTKI targeting VEGFR, PDGFR, FGFR, and c-Kit; Table 1 ) in female tumor-bearing mice.…”
Section: Diffusion and Abp-mediated Mechanisms Could Underlie The Accumulation Of Rtkis Bound To Albumin In Healthy Organs And Tissuessupporting
confidence: 87%
“…We conjugated HSA with FNR648 fluorescence dye following the procedure described in our previous publication 55.…”
Section: Methodsmentioning
confidence: 99%
“…It’s commonly used in synthesis of functional polymers, cell markers, and biomedical synthesis. 20 , 21 Stefanucci Azzurra’s team reported a new enkephalin analogue with great analgesic, which was constructed via “click chemistry”; 22 Lee’s team used copper-free “click chemistry” to combine growth factors with collagen. 23 “Click chemistry” is a powerful synthetic tool in the discovery of new drugs.…”
Section: Introductionmentioning
confidence: 99%